2016
DOI: 10.1038/srep31403
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of an engineered isolate of Lactobacillus plantarum with enhanced raffinose metabolic capacity

Abstract: Lactic acid bacteria that can produce alpha-galactosidase are a promising solution for improving the nutritional value of soy-derived products. For their commercial use in the manufacturing process, it is essential to understand the catabolic mechanisms that facilitate their growth and performance. In this study, we used comparative proteomic analysis to compare catabolism in an engineered isolate of Lactobacillus plantarum P-8 with enhanced raffinose metabolic capacity, with the parent (or wild-type) isolate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…These proteins were associated with carbohydrate transport and metabolism. Several proteomic studies found an increase in the expression of this group of protein when the culture shifted from the exponential growth phase to the stationary phase (Laakso et al, 2011;Wang et al, 2016). Our study observed that the adapted strain (wild type) grew better than the asp23 gene deletion mutant in the gentamycin-containing medium; thus, such protein expression changes could be regarded as signatures of phase transition of the asp23 mutant.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…These proteins were associated with carbohydrate transport and metabolism. Several proteomic studies found an increase in the expression of this group of protein when the culture shifted from the exponential growth phase to the stationary phase (Laakso et al, 2011;Wang et al, 2016). Our study observed that the adapted strain (wild type) grew better than the asp23 gene deletion mutant in the gentamycin-containing medium; thus, such protein expression changes could be regarded as signatures of phase transition of the asp23 mutant.…”
Section: Discussionsupporting
confidence: 52%
“…In the L. casei Zhang genome, the former 5 proteins are located within the same gene cluster that is responsible for the de novo synthesis of fatty acids (Zhang et al, 2010). Similarly, 4 of the downregulated carbohydrate utilization-related proteins were clustered, and they were involved in the sorbitol metabolism (Wang et al, 2016). These proteins included the PTS system sorbitol transporter subunits EIIA (LCAZH_2727), EIIBC (LCAZH_2728), and EIIC (LCAZH_2729) and sorbitol-6-phosphate dehydrogenase (LCAZH_2732).…”
Section: Differentially Expressed Proteins In the Wild-type Strain Comentioning
confidence: 99%
“…For instance, Ultra-Performance Liquid Chromatography (UPLC) is highly advised because to its high sensitivity and precision, minimal solvent usage, high efficiency, and high resolution (Dong & Guillarme, 2013). Recent research has demonstrated that UPLC will be recommended due to its superior capacity for postbiotic separation and identification; this technique was used in the profile identification of compounds present in intracellular content of L. plantarum (Wang et al, 2016) and the intracellular protein profile in Lactobacillus mucosea (e.g., thioredoxin, phosphoglycerate kinase, cysteine synthase) (Pajarillo et al, 2015). Similar to this, antifungal metabolites produced by L. brevis P68 have been characterized by mass spectrometry, infrared, carbon-13 and 1 H-NMR, and electro-spray ionization (Arasu et al, 2015).…”
Section: Methodologies To Identify and Obtain Postbioticsmentioning
confidence: 99%
“…Peptides were analyzed by 4–20% tricine sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS–PAGE) and visualized by Coomassie Blue staining. The amino acid compositions and concentrations of keratin fractions were quantified using a Hitachi automatic amino acid analyzer L-8900 (Hitachi High-Technologies Co., Tokyo, Japan) with an ion-exchange column (4.6 mm inner diameter, 60 mm length, and 3 μm particle size) to separate amino acids as described previously …”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, lyophilized samples (0.5 mL) from the Superdex 30 pg column were dissolved in deionized water and loaded at a flow rate of The amino acid compositions and concentrations of keratin fractions were quantified using a Hitachi automatic amino acid analyzer L-8900 (Hitachi High-Technologies Co., Tokyo, Japan) with an ion-exchange column (4.6 mm inner diameter, 60 mm length, and 3 μm particle size) to separate amino acids as described previously. 35 Liquid Chromatography and Mass Spectrometry. Purified keratin fractions were analyzed by reverse-phase ultra-performance liquid chromatography−electrospray ionization−tandem mass spectrometry (UPLC−ESI−MS/MS) using a ACQUITY I-Class (Waters) directly connected to an SCIEX TripleTOF 5600+ mass spectrometer in direct injection mode, as described previously.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%